Progressive Islam in the Asian context: need for building Islam and Buddhism relations - Yusuf, Imtiyaz (2019)
This paper presentation stresses the importance for Islamic Studies in Muslim countries to integrate the study and research about Buddhism. Buddhism is not a new religion for the Muslims. Muslim scholars have studied and written about Buddhism since their 8th century arrival in Asia.